“Developing Capabilities”. Inclusive Extracurricular Enrichment Programs to Improve the Well-Being of Gifted Adolescents - Casino-García, Ana María; Llopis-Bueno, María José; Gómez-Vivo, María Gloria; Juan-Grau, Amparo; Shuali-Trachtenberg, Tamar; Llinares-Insa, Lucía I. (Frontiers in Psychology, 2021)
The educational inclusion of gifted students requires not only equity but also emotional accessibility and social participation. However, different studies indicate that gifted students constitute a vulnerable group (for example, the incidence of bullying is higher). Psychosocial variables are determinants for the development and expression of giftedness, particularly during adolescence. This study analyzes the impact of an inclusive extracurricular enrichment program for gifted secondary school students on the well-being of adolescents. The program was based on the enrichment model of Renzulli and Reis (2016). The objective was to develop a cluster to facilitate high-achieving learning in collaboration with teachers, administrators, and guidance counselors from their schools as well as university professors and students that would address their emotions and socialization across the board and benefit or involve their peers in their regular classrooms. The intervention took place over two years: eight sessions, one afternoon per week, for five months during each school year. The sample consisted of 47 students from the first and second years of compulsory secondary education (Educación Secundaria Obligatoria - ESO) (age, mean (M) = 12.57, standard deviation (SD) = 0.82) during the first year and 27 students from the first, second, and third years of ESO (age, M = 13.48, SD = 0.94) during the second year; 61.4% were girls. Participants completed a questionnaire before (T1) and (T3) and after (T2) and (T4) each intervention. The results show better outcomes for psychological and subjective well-being, more positive moods, and a significant reduction in school fears. The results from this study indicate the importance of educational screening and support for gifted students to promote their well-being through collaborative enrichment activities.